Feasibility of ureteroscopy as a pure day-case procedure. (July 2019) - Grice, PT; Phillips, OP; Khan, MA
Objective: Ureteroscopy (URS) is a procedure that is commonly performed by endourologists for stone surgery and other diagnostic and therapeutic indications. With stone disease becoming an increasing burden on the health economy, there is a clear incentive to perform URS as a day-case procedure. Patients and methods: This single-centre, single-surgeon study prospectively considered all patients for day-case rigid or flexible URS over a 12-month period, with the only exclusion criteria being an American Society of Anesthesiologists score greater than 3 or a lack of aftercare. Results: Sixty-six patients were included with 61 being discharged the same day of surgery, meaning a pure day-case rate of 92% and 30-day postoperative readmission rate of 6%. Conclusion: This study suggests that URS should primarily be considered a day-case procedure whenever feasible. Level of evidence: 2c